2018
DOI: 10.1080/08869634.2018.1512197
|View full text |Cite
|
Sign up to set email alerts
|

Is PostureScreen® Mobile app an accurate tool for dentists to evaluate the correlation between malocclusion and posture?

Abstract: Dental occlusion anomalies and posture pathological modifications can be inter-related. PostureScreen® Mobile app might represent a useful tool in the early diagnosis of dental occlusion pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…These data suggest caution using the PSM app when highly accurate postural assessments are necessary. Instead, innovative use of this technology is proposed by Iacob et al [ 101 ], which tested the PSM app to evaluate dental occlusion anomalies. Both static and dynamic occlusion were evaluated.…”
Section: Mobile Application and Wearable Devices For Posture Managementmentioning
confidence: 99%
“…These data suggest caution using the PSM app when highly accurate postural assessments are necessary. Instead, innovative use of this technology is proposed by Iacob et al [ 101 ], which tested the PSM app to evaluate dental occlusion anomalies. Both static and dynamic occlusion were evaluated.…”
Section: Mobile Application and Wearable Devices For Posture Managementmentioning
confidence: 99%
“…[66] Scoliosis [67] Rib Hump Angle/Scoliosis [68] Kyphotic Angles [69] Cobb Angle/Thoracic Scoliosis [70] Cobb Angle/Thoracic Scoliosis [71] Lumbar Lordosis [72] Rib Hump Angle/Scoliosis Evaluation [73] Cobb Angle of Thoracolumbar Scoliosis [74] Cobb Angle [75] Cobb Angle [76] Cobb Angle [77] Head, Ribcage, Shoulder, Hip and Knee Tilt [65] Inclination of the Human Spinal Points [78] SS and Lumbar Curve [79] PI, PT and LL [80] Sagittal Curvaures [81] Thoracic Spine Rotation [82] LL, PI, and PT [83] Head, Ribcage, Shoulder, Hip Tilt [84] Head, Ribcage, Shoulder, Hip Inclination [85] Scoliosis Angle [86] Head, Shoulder and Ribcage Tilt [87] Head, Ribcage, Shoulder, Hip and Knee Tilt [88] LL, PI, SS and PT [89] LL, PT, and SS [90] Rib Hump/Scoliosis Evaluation Note: LL = Lumbar Lordosis; PI = Pelvic Incidence; SS = Sacral Slope; PT = Pelvic Tilt.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…Table 10 presents the studies organized in this classification. [77,83,84,86,87] Among the studies identified, only one reported use of machine learning algorithms in the proposed mobile application. Estrada and Vea [65] developed a solution to detect proper/improper sitting postures based on the angles of the spinal curvatures.…”
Section: Study Measures Takenmentioning
confidence: 99%
See 2 more Smart Citations